Acute-on-Chronic Liver Failure From Chronic-Hepatitis-B, Who Is the Behind Scenes - Li, Qian; Wang, Jun; Lu, Mengji; Qiu, Yuanwang; Lu, Hongzhou (Frontiers in Microbiology, 2020)
Acute-on-chronic liver failure (ACLF) is an acute syndrome accompanied with decompensation of cirrhosis, organ failure with high 28-day mortality rate. Systemic inflammation is the main feature of ACLF, and poor outcome is closely related with exacerbated systemic inflammatory responses. It is well known that severe systemic inflammation is an important event in chronic hepatitis B (CHB)-ACLF, which eventually leads to liver injury. However, the initial CHB-ACLF events are unclear; moreover, the effect of these events on host immunity as well as that of immune imbalance on CHB-ACLF progression are unknown. Here, we investigate the initial events of ACLF progression, discuss possible mechanisms underlying ACLF progression, and provide a new model for ACLF prediction and treatment. We review the characteristics of ACLF, and consider its plausible immune predictors and alternative treatment strategies.